Respuesta :

Answer:

[tex](x - y)(x + y + 1)[/tex]

Step-by-step explanation:

[tex]x(x + 1) - y(y + 1)[/tex]

[tex]=> x^{2} + x - y^{2} - y[/tex]

Lets re-arrange it.

[tex]=> x^{2} - y^{2} + x - y[/tex]

Now , lets expand x² - y².

[tex]=> (x + y)(x - y) + (x - y)[/tex]

Taking ( x - y ) common ,

[tex]=> (x - y)(x + y + 1)[/tex]

Answer:

[tex]x(x + 1) - y(y + 1) \\ → {x}^{2} + x - {y}^{2} - y \\→( {x}^{2}- {y}^{2}) + (x - y) \\→ (x - y)(x + y) + (x - y) \\→ \boxed{ (x - y)(x + y + 1)}✓[/tex]

(x-y)(x+y+1) is the right answer.